Hybridization-based discovery of novel quinazoline-2-indolinone derivatives as potent and selective PI3Kα inhibitors - Changqun Liu; Yuening Cao; Yi Zuo; Chaozheng Zhang; Senmiao Ren; Xin Zhang; Chuanqi Wang; Yingjie Zeng; Jie Ling; Yilan Liu; Zixian Chen; Xiujun Cao; et al. (Journal of Advanced Research)
Introduction: Phosphatidylinositol 3-kinases (PI3Ks) overexpression can elicit cellular homeostatic dysregulation, which further contributes to tumorigenesis, with PI3Kα emerging as the most prevalent mutant isoform kinase among PI3Ks. Therefore, selective inhibitors targeting PI3Kα have attracted considerable interest in recent years. Molecular hybridization, with the advantage of simplified pharmacokinetics and drug-drug interactions, emerged as one of the important avenues for discovering potential drugs. Objectives: This study aimed to construct PI3Kα inhibitors by hybridization and investigate their antitumor activity and mechanism. Methods: 26 quinazoline-2-indolinone derivatives were obtained by molecular hybridization, and their structure–activity relationship was analyzed by MTT, in vitro kinase activity and molecular docking. The biological evaluation of compound 8 was performed by transwell, flow cytometry, laser scanning confocal microscopy, Western blot, CTESA and immunohistochemistry. Results: Here, we employed molecular hybridization methods to construct a series of quinazoline-2-indolinone derivatives as PI3Kα selective inhibitors. Encouragingly, representative compound 8 exhibited a PI3Kα enzymatic IC50 value of 9.11 nM and 10.41/16.99/37.53-fold relative to the biochemical selectivity for PI3Kβ/γ/δ, respectively. Moreover, compound 8 effectively suppressed the viability of B16, HCT116, MCF-7, H22, PC-3, and A549 cells (IC50 values: 0.2 μM ∼ 0.98 μM), and dramatically inhibited the proliferation and migration of NSCLC cells, as well as induced mitochondrial apoptosis through the PI3K/Akt/mTOR pathway. Importantly, compound 8 demonstrated potent in vivo anti-tumor activity in non-small cell lung cancer mouse models without visible toxicity. Conclusions: This study presented a new avenue for the development of PI3Kα inhibitors and provided a solid foundation for novel QHIDs as potential future therapies for the treatment of NSCLC.